2020
DOI: 10.3389/fimmu.2020.00324
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E Receptor 4 Antagonist in Cancer Immunotherapy: Mechanisms of Action

Abstract: A highly expressed prostaglandin E 2 (PGE 2) in tumor tissues suppresses antitumor immunity in the tumor microenvironment (TME) and causes tumor immune evasion leading to disease progression. In animal studies, selective inhibition of the prostaglandin E receptor 4 (EP4), one of four PGE 2 receptors, suppresses tumor growth, restoring the tumor immune response toward an antitumorigenic condition. This review summarizes PGE 2 /EP4 signal inhibition in relation to the cancer-immunity cycle (C-IC), which describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 44 publications
(59 reference statements)
2
45
0
Order By: Relevance
“…In cancer, the most abundant COX-2 product is prostaglandin E 2 (PGE 2 ) which binds four G-protein-coupled EP receptors (EP1-EP4) to activate several intracellular signaling pathways. EP4 is upregulated and contributes to the pathology of many human malignancies including those of the breast, prostate, colon, ovary, and lung (Reader et al, 2011;Majumder et al, 2018;Take et al, 2020). EP4 receptor signaling is linked to many properties of malignant cells including proliferation, migration, invasion, metastasis, angiogenesis, immune evasion, epithelial to mesenchymal transition, and cancer stem cell (CSC) properties.…”
Section: Ep4 In the Malignant Cellmentioning
confidence: 99%
See 2 more Smart Citations
“…In cancer, the most abundant COX-2 product is prostaglandin E 2 (PGE 2 ) which binds four G-protein-coupled EP receptors (EP1-EP4) to activate several intracellular signaling pathways. EP4 is upregulated and contributes to the pathology of many human malignancies including those of the breast, prostate, colon, ovary, and lung (Reader et al, 2011;Majumder et al, 2018;Take et al, 2020). EP4 receptor signaling is linked to many properties of malignant cells including proliferation, migration, invasion, metastasis, angiogenesis, immune evasion, epithelial to mesenchymal transition, and cancer stem cell (CSC) properties.…”
Section: Ep4 In the Malignant Cellmentioning
confidence: 99%
“…There is growing evidence that EP4 represents a novel therapeutic target in cancer, both expressed on the malignant cell as well as on EP4-positive host cells. It is likely that EP4 antagonists would be used in combination with either cytotoxic therapies or with other immune-modulating strategies (for excellent reviews see Majumder et al, 2018;Take et al, 2020). There is growing evidence that EP4 blockade can reverse chemotherapy resistance in several tumor types and therefore combinations of EP4 antagonists with standard of care chemotherapy should be considered.…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistently, activating PPARG might be a potential mechanism of AA inhibiting M2 polarization. In addition, PGE2-EP4 signaling has been reviewed as a possible mechanism to M2 polarization (Take et al, 2020), while in our polarization model, we found PGE2 increased M2 polarization even though EP4…”
Section: Discussionmentioning
confidence: 55%
“…Given the multiple tumor-promoting roles of EP4 expression on tumor cells and host immune cells and endothelial cells, we suggest that combination of EP4 antagonists and other immunomodulating drugs should work synergistically, especially in TNBCs displaying a diverse microenvironment. Excellent reviews by Fulton et al [139] and Take et al [140] strongly suggest the potential benefit of EP4 antagonist in combination with other immunomodulating agents in cancer therapy.…”
Section: Ep4 Antagonists Used In Combination Therapiesmentioning
confidence: 99%